Sustainable biosynthesis, physiochemical characterization, cytotoxicity, and antimicrobial evaluation of novel chromium oxide nanoparticles - Elshazly, Ezzat H.; Abd elfadeel, G.; Yang, Lihang; Li, Xiqi; Ewais, Emad A.; Sadek, Ahmed M.; Taha, Taher M.; Fathy, Omar; Atta, Omar Mohammad; Liu, Wen-Zong (Frontiers in Chemistry, 2025)
The biosynthesis of nanoparticles (NPs) has attracted significant interest due to their diverse biological applications. However, the potential for NPs synthesis using plant resources from Vicia monantha Retz remains largely unexplored. Notably, this study marks the first use of this specific plant for the biosynthesis of chromium oxide nanoparticles (Cr2O3NPs). In the present study, the single phase of Cr2O3 was confirmed at a calcination temperature 700 °C for the synthesized NPs. The crystallite sizes increased from 14 nm to 20 nm with the increase in the calcination temperature to 900 °C for 2 h. Ultraviolet–visible (UV–VIS) light spectroscopy revealed that the samples are semiconductor materials, according to the observed values of energy band gap. The developed Cr2O3NPs did not show any toxicity toward NIH-3T3 fibroblasts. The results demonstrated that Cr2O3NPs exhibited good antimicrobial activity against two bacterial strains (Escherichia coli and Staphylococcus aureus) and two fungal strains (Candida albicans and Aspergillus sp.), producing clear inhibition zones of 0.26 cm, 0.21 cm, 0.28 cm, and 0.3 cm, respectively, after 24 h. The Cr2O3NPs exhibit successful green synthesis, notable biocompatibility, and antimicrobial properties, making them highly promising for various applications and opening possibilities for the utilization of nanoparticles in antimicrobial systems.